SEPIC Converter based-Drive for Unipolar BLDC Motor - Raghu Thumu; S. Chandra Sekhar; J. Srinivas Rao (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Front-end single-ended primary inductance converter (SEPIC) and a switch in series with each phase is proposed for driving a permanent magnet brushless dc (BLDC) motor with unipolar currents. All the switches are ground-referenced, which simplifies their gate drives. The available input voltage can be boosted for better current regulation, which is an advantage for low voltage applications. The SEPIC converter is designed to operate in the discontinuous conduction mode for operation with an ac supply. In this operation mode, the line current follows the line voltage waveform to a certain extent. The reduction in low-order harmonics and improved power factor is achieved without the use of any voltage or current sensors. The simplicity and reduced parts count of the proposed topology make it an attractive low-cost choice for many variable speed drive applications. The proposed topology is simulated and verified by using MATLAB/SIMULINK.DOI:http://dx.doi.org/10.11591/ijece.v2i2.306